Major players: bureaucracies in American government - Kaufman, Herbert (2001)
For more than 50 years, Herbert Kaufman has been an astute observer of public bureaucracies. In this essay, Kaufman draws on his extensive experience in explaining the role of public bureaucracies in the American political system. Kaufman was motivated to write the essay because of his concern that public bureaucracies are not given adequate attention in American government textbooks. We hope that PAR readers will use the essay to educate students and others about the important role of public bureaucracies in American government. - Reproduced
Keywords: Civil service - United States; Civil service